(untitled) (Journal of the College of Education for Women, 2019)
Harold Pinter’s The Caretaker(1959) clearly portrays a lack of communication among the characters of the play which refers to the condition of modern man. This failure of communication led Harold Pinter to use a lot of pauses and silences in all the plays he wrote instead of words. Samuel Beckett preceded Pinter in doing so in his plays and one way to express the bewilderment of modern man during the 20th century is through the use of no language in the dramatic works. Language is no more important to modern man; instead, he uses silence to express his feelings. Silence is more powerful than the words themselves. That’s why long and short pauses can be seen throughout all Pinter’s plays. In this play, the characters choose not to communicate; instead, they keep silent because they fail to interact with each other or even with themselves. That is the condition of modern man in which there is no place for such things like understanding or even sharing and this could be one reason behind the physical absence of female figures in this play. Pauses are used to portray the concept that language is a vague and meaningless tool people use to hide their own discomfort. The pauses indicate that to fill the silent gap a person must think about what they are going to say to fill it. More can be said during the pauses and silences than in the actual dialogue.